Full-Length Transcriptome Sequencing and Comparative Transcriptomics Reveal the Molecular Mechanisms Underlying Gonadal Development in Sleepy Cod (Oxyeleotris lineolata) - Jiajia Fan; Dongmei Ma; Huaping Zhu; Minghui Lin; Zaixuan Zhong; Yuanyuan Tian (Biology)
Sleepy cod (Oxyeleotris lineolata) is native to Australia and is now an economically valuable fish cultured in China and Southern Asian countries. Its growth rate exhibits as sexually dimorphic, with males generally growing more rapidly and attaining a larger body size compared to females. Thus, the effective development of sex control breeding can significantly contribute to increased yields and output value. Nevertheless, due to the lack of genomic and transcriptomic data, the molecular mechanisms underlying sex determination and gonadal differentiation in sleepy cod remain poorly understood. In this study, long-read PacBio isoform sequencing (Iso-Seq) was performed to obtain a full-length transcriptome from a pooled sample of eight tissues (kidney, brain, liver, muscle, heart, spleen, ovary and testis). A total of 30.41 G subread bases were generated and 49,113 non-redundant full-length transcripts with an average length of 2948 bp were produced. Using the full-length transcriptome as a reference, short-read Illumina sequencing was performed to investigate the differences in gene expression at the transcriptome level between ovaries and testes from 12-month-old individuals. A total of 19,102 differentially expressed transcripts (DETs) were identified, of which 8510 (44.55%) were up-regulated in the ovary and 10,592 (55.45%) were up-regulated in the testis. The DETs were mainly clustered into 241 KEGG pathways, in which oocyte meiosis and arachidonic acid metabolism were the most relevant pathways involved in gonadal differentiation. To verify the validity of the transcriptomic data, 20 DETs were selected to investigate the gonad expression profiles based on qPCR. The expression levels of all 20 screened genes were consistent with the transcriptome sequencing results. The present study provides new genetic resources—including full-length transcriptome sequences and annotation information—as a coding genomic-level reference for sleepy cod—yielding valuable insights into the genetic mechanisms of sex determination and gonadal differentiation in this economically important species.